A bi-layer buffer system AlN/Al1−xInxN to enable the growth of high crystal quality Al0.36In0.64N thin films on Si (111). Issue 35 (30th July 2019) - Lu, Wei; Wang, Xiaoyi; Ma, Yongjun; Grasso, Salvatore; Xu, Ming
Abstract : We report a unique AlN/AlInN bi-layer buffer design to enable the growth of textured c -axis wurtzite Al0.36 In0.64 N epilayer on a Si (111) substrate, which creates the possibility to grow high crystal quality Al0.36 In0.64 N. Abstract : We report a low-power and low-temperature radio frequency reactive magnetron sputtering to grow highly c -axis oriented wurtzite Al0.36 In0.64 N thin films on a Si (111) substrate using a unique AlN/AlInN bi-layer buffer, which creates the possibility to grow high crystal quality Al0.36 In0.64 N.